2020
DOI: 10.3389/fbioe.2020.611900
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Path Optimization for Efficient Production of 2′-Fucosyllactose in an Engineered Escherichia coli C41 (DE3) Derivative

Abstract: 2′-fucosyllactose (2′-FL), one of the simplest but most abundant oligosaccharides in human milk, has been demonstrated to have many positive benefits for the healthy development of newborns. However, the high-cost production and limited availability restrict its widespread use in infant nutrition and further research on its potential functions. In this study, on the basis of previous achievements, we developed a powerful cell factory by using a lacZ-mutant Escherichia coli C41 (DE3)ΔZ to ulteriorly increase 2′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…Overexpression of rcsA and/or rcsB generally led to an obvious enhancement of 2′-FL in previous studies. 14,16,29 Drouillard et al developed a method for 2′-FL production by high-celldensity fermentation of an engineered E. coli strain only overexpressing rcsA and H. pylori f utC genes and inactivating the wcaJ gene. The maximum 2′-FL titer reached 3 g/L intracellularly and 11 g/L extracellularly from the initially added lactose at 15 g/L after fermentation for 45 h. 29 The 2′-FL concentration was greatly improved to 2.12 g/L in the engineered strain expressing rcsA gene, representing a 58.2% increase in comparison with that in the control strain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of rcsA and/or rcsB generally led to an obvious enhancement of 2′-FL in previous studies. 14,16,29 Drouillard et al developed a method for 2′-FL production by high-celldensity fermentation of an engineered E. coli strain only overexpressing rcsA and H. pylori f utC genes and inactivating the wcaJ gene. The maximum 2′-FL titer reached 3 g/L intracellularly and 11 g/L extracellularly from the initially added lactose at 15 g/L after fermentation for 45 h. 29 The 2′-FL concentration was greatly improved to 2.12 g/L in the engineered strain expressing rcsA gene, representing a 58.2% increase in comparison with that in the control strain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a previous study, the single expression of rcsA and coexpression of rcsA and rcsB both promoted GDP-Lfucose synthesis obviously in E. coli and the coexpression of rcsA and rcsB exhibited a better promotion effect than single expression of rcsA; in addition, the enhanced GDP-L-fucose supply favored to improve 2′-FL biosynthesis. 16 Integration of wbgL in recA Locus of the Engineered Host. Considering the supply of the GDP-L-fucose pathway via the overexpression of genes manC, manB, gmd, wcaG, rcsA, and rcsB, we speculated that a great increase in 2′-FL production might be obtained by further strengthening the expression of gene wbgL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was indicated that the expression of LgtA on low-copy plasmid pACYCDuet-1 was beneficial for LNnT synthesis. Taken together, combinatorial optimization strategy via changing different plasmids has been widely used as a practical strategy for in vivo highly efficient production of other HMOs, such as 2′-fucosyllactose (2′-FL), , 3-fucosyllactose (3-FL), and LNTri II …”
Section: Resultsmentioning
confidence: 99%
“…This method deleted the lacZ , gcd , glK , ptsG , and pfKA genes to overexpress the de novo UDP-D-galactose and GDP- l -fucose pathways, and used sugar efflux transporters to promote the export of 2′-FL. They increased the production of 2′-FL to 60 g/L after 48 h. The use of glycerol as a carbon source by Ni et al can also ensured reduced costs. They deleted genes involved in the degradation of precursors GDP- l -fucose and GDP-mannose, and further expanded production by introducing two heterologous positive regulators.…”
Section: Hmos Production Using Microbial Systemsmentioning
confidence: 99%